PENGARUH MEDIA VIDEO PEMBELAJARAN TERHADAP MINAT DAN HASIL BELAJAR IPA SISWA KELAS VI SDN 6 KAYUMALUE NGAPA - Viviantini, Viviantini (JSTT, 2015)
The objective of the study was to determine the effect of instructional video media toward the interest and students learning outcomes. This study is descriptive quantitative by quasy experiment. The subject of the study ware the students of sixth grade, it’s a number 25 of A-class as a treatment and 25 of B-class as a control research. The data was collected by questioner and achievement test. The data analysis by used simple regression, which begins prerequisite test, normality and homogeneity at trusty level at 95%. Based on the results, It’s obtained tcount = 4.56 with ttable = 0.140. The study findings was a difference in student learning outcomes were taught by using video media with the conventional class. They differ in learning outcomes and interest because the effect of using video media at sixth grade SDN 6 Kayumalue Ngapa.